Potential production of biodiesel from green microalgae. Issue 2 (17th February 2020) - Tulashie, Samuel Kofi; Salifu, Siisu
ABSTRACT: This work involves the study of the potential production of biodiesel from green microalgae. The green microalgae were cultured and treated with different nutrient concentrations of 0, 0.175, 0.35, 2 and 4 g in the laboratory where they were later centrifuged. The 4 g treatment had the highest growth of 0.186 cell/h, followed by the 2 g treatment of 0.151 cell/h within 24 h. The 0, 0.175 and 0.35 g had similar growth rates which were lower than the 4 and 2 g. Oil was extracted from the centrifuged cultured algae sample and the raw algae sample using hexane via Soxhlet extractor. The total oil extracted from 15 g of the centrifuged sample dry biomass and 30 g of the raw sample dry biomass were 2.038 and 3.826 g, giving a yield of 13.6 and 12.8%, respectively. The amounts of hexane recovered from the centrifuged sample and the raw sample were 46.67 and 53.33%, respectively. The results suggest hexane can be used to extract algal oil which can be transesterified to biodiesel which is more environmentally friendly than fossil diesels.